Neurocysticercosis: Is Medical Management Innocuous? - Guinto, Gerardo; Guinto-Nishimura, Yoshiaki (My University, 2013)
Cysticercosis continues to be the most common parasitic infection of the human central nervous system (CNS). It is produced by the larvae of Taenia solium, whose life cycle, both man and pig, participate as intermediate hosts, but humans are the definitive host. Accidental consumption of pork contaminated with cysticerci results in the intestinal form of the disease known as taeniasis, where the tapeworm can remain in the gut for years, often without causing any sign or symptom. The host constantly releases the tapeworm eggs, which are excreted through feces. When a person (who could be the same carrier) eats foods contaminated with these feces, the eggs reenter the gastrointestinal tract but are then transformed into oncospheres capable of crossing the intestinal wall and reaching the bloodstream, where they travel through the body, finally residing in certain tissues such as muscle, eye, and especially the CNS, establishing the diagnosis of neurocysticercosis (NCC).